Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 5 - Exponential Functions - 5.2 Solving Equations Using Exponent Rules - 5.2 Exercises: 52

Answer

$t = 6$

Work Step by Step

$-6(2^{t}) - 25 = - 409$ $-6(2^{t}) = -409 + 25$ $-6(2^{t}) = -384$ $2^{t} = 64$ $2^{t} = 2^{6}$ $t = 6$ Check: $ -6(2^{t}) - 25$ $= -6(2^{6}) - 25$ $= -6(64) - 25$ $= -384 - 25$ $= -409$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.